Optimalisasi Pendidikan Aswaja pada Generasi Milenial sebagai Upaya Deradikalisasi (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2019)
Radicalism is a increasingly prevalent phenomenon in Indonesia for recentyears. Radicalism increasingly developed when ‘orde baru’ (soeharto's regime)ended. The reform era is expanding space for people to express their feeling,including expressions of diversity. Including indicators of the emergence ofradicalism in Indonesia is the birth of religious organizations that often use violentmethods in carrying out its mission. Various radical Islamic organizations havevarious characteristics, variants and also orientations. However, there aresimilarities between radical Islamic organizations, namely the use of violence thatcame to be known as terror. Unfortunately almost of groups are dominated bymillennial generation. This problem is a concern for the wider communitysurely.Various efforts to respond radicalism also appears contra ideology betweenthem too. Aswaja education proved be able to prohibit radicalism viruses.This article will present data from interviews, observations, and literaturereviews related to the topic. The arguments which built in this paper arereconstruction and actualisation values which contained in Aswaja can bestrongly internalized in person's life, especially millenial generation. The properaswaja socialization and internalization is trough education. In schools, colleges,and study forums which apply aswaja content; students, college students, and thestudy participants will have opportunity to have moderate religion understandingand will be far away from radicalism diseases.